'Off colour' alpaca. Issue 8 (3rd September 2015) - Turner, Andrea
Abstract : THIS series gives readers the opportunity to consider and contribute to discussion of some of the ethical dilemmas that can arise in veterinary practice. Each month, a case scenario is presented, followed by discussion of some of the issues involved. In addition, a possible way forward is suggested; however, there is rarely a cut‐and‐dried answer in such cases, and readers may wish to suggest an alternative approach. This month's dilemma, '"Off colour" alpaca?', was submitted and is discussed by Andrea Turner. Readers with comments to contribute are invited to send them as soon as possible, so that they can be considered for publication in the next issue. Discussion of the dilemma 'Billy the kid', which was published in the July/August issue of In Practice, appears on page 431. The series is being coordinated by Siobhan Mullan, of the University of Bristol. It is hoped it will provide a framework that will help practices find solutions when facing similar dilemmas.